A Theoretical Analysis of Smuggling - Bhagwati, Jagdish; Hansen, Bent (Quarterly Journal of Economics, 1973)
I. Smuggling and welfare, 173. — II. Exogenously specified objectives: target increase in importable production, 184. — III. Overinvoicing and underinvoicing of transactions, 186. — IV. Conclusions, 187.